Parceria público-privada na rede municipal de educação de Marmeleiro – PR: implicações para a formação continuada e organização do trabalho docente - Nercolini, Graciela (2021)
The objective of this dissertation is to analyze the main implications of the adoption of the apostilado system of private education for the continuing education and organization of the teaching work of elementary school of the municipal education network of Marmeleiro (PR), between the years 2009 to 2021, as well as to identify how this partnership occurred between the public administration of the municipality of Marmeleiro (PR) with the private education system of Grupo Positivo, which provides teaching material, pedagogical advice, training for teachers and access to the digital platform LearnS Brazil On. For this purpose, a qualitative approach was used, and the methodology was based on the documentary and bibliographic study on the conjuncture of international macro policy and its repercussion on national policy. Three points of the guide organize this research. In the first chapter, there are brief considerations about the capital crisis, neoliberalism, State reform, educational policy, education, public-private partnerships in Brazil. We analyze and discuss the main mechanisms of insertion of entrepreneurs in Brazilian public education. In the second, we made a brief historical rescue of the municipality of Marmeleiro-PR, as well as its main geographical, political, economic, cultural and educational aspects. In addition, we presente the contextualization and legal procedures related to the signing of the contract between Positivo Ltda Publishing House and the City Hall. In the third chapter, it points out the main pedagogical implications arising from the "partnership" signed between Editora Positivo and the Municipality of Marmeleiro-PR. At this moment, we describe and analyze the positivo group's view of teaching work and performance, the autonomy of teachers through the use of the apostilate education system and, finally, the quality of education according to the model imposed on the collectively constructed. The emphasis turns to the public-private "partnerships" in education, as well as its implications for the continuing education and work of elementary school teachers – Initial years of the municipal education network of Marmeleiro (PR), between the years 2009 to the present date.